Analysis Of Market Segmentation Based on Geographic, Demographic, Psychographic, And Behavior in CV Hoeda Kharya Santoesa - Huda, Miftakh Nur (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
Market segmentation is the classification of markets in different groups aiming to carry out marketing according to characteristics, needs and desires. The domestic apparel and textile industry is still in decline due to changes in people’s consumption patterns during the Covid-19 pandemic. In terms of garment industry potential and segmentation problems in CV Hoeda Kharya Santoesa. Research was the quantitative descriptive, used in this research was the purposive sampling. A number of samples used in this research were 100 samples for data collecting was distributing questionnaires. Respondents in this research are about 110 people. With tools SPSS version 25.0 the data obtained was tested for validity and reliability. Data that has been valid and reliable to be processed through cluster analysis using a non-hierarchical clustering procedure k-means method. The results of this study resulted in three different segments, namely 1) cooperative customer segment (44.5%) customer group who don’t notice to company location, but notice a demographic, psychographic and behavioral factors, 2) mid income user (39.1%) customer group who notice to all aspects, 3) growing customer segment (16.4%) customer group who prioritize demographic factors. Each segment has different characteristics, profiles, and behaviors. CRM is implemented to build stronger relationships by tailoring interactions and offers to the behavioral preferences of customers and potential customers.